Impacto socioeconómico de la minería metálica en la parroquia Gualel del cantón Loja y su influencia en el desarrollo de las comunidades locales, desde un enfoque cualitativo - Valdivieso Ortega, Juan Emanuele (2024)
The mining concessions in Loja have triggered intense debates: some see opportunities, other fear negative impacts on the environment and traditional practices. Addressing these challenges responsibly is essential to balance the economic development, environmental preservation, and community well-being. The purpose of this study is to analyze the socioeconomic impact of the metal mining in the parish of Gualel of the canton of Loja and its influence on the development of local communities. This study was carried out through a qualitative approach that involves the application of semi-structured interviews, which are processed by using NVivo software. Moreover, a nonparticipant observation was incorporated to complement the research. The main results derived from the study showed that mining benefited the local economy, creating employment sources and increasing incomes, but also generated social conflicts, then it can be determined that metallic mining not only generates economic wealth, but also has a transforming impact on communities and environments. Therefore, its management must be oriented towards the long-term future.